A note on Köthe-Toeplitz duals of certain sequence spaces and their matrix transformations - B. Choudhary; S. K. Mishra (International Journal of Mathematics and Mathematical Sciences, 1995)
In this paper we define the sequence spaces Sℓ∞(p), Sc(p) and Sc0(p) and determine the Köthe-Toeplitz duals of Sℓ∞(p). We also obtain necessary and sufficient conditions for a matrix A to map Sℓ∞(p) to ℓ∞ and investigate some related problems.